МИЙНЕТ САБАҒЫНДА ЭЛЕКТРОМОНТАЖ ЖУМЫСЛАРЫ БОЙЫНША АЙЫРЫМ ШЫНЫҒЫЎЛАРДЫ ТЕХНОЛОГИЯЛЫҚ КАРТА ТИЙКАРЫНДА ӨТИЎ МЕТОДИКАСЫНЫҢ ӨЗГЕШЕЛИКЛЕРИ - Курманов, А. (FAN va JAMIYAT, 2016)
The article deals with the basis of the developed calendar-thematic plan, giving students basic information about electrical current and explaining the sources of electrical energy and the spheres of its application.